Novostavba bytového domu - Navrátilová, Vladimíra (Vysoké učení technické v Brně. Fakulta stavební, 2020)
Téma bakalářské práce je novostavba bytového domu. Objekt je určen pro bydlení a také služby. Je situován na rovné parcele. Stavba má tři nadzemní podlaží bez sklepu. Budova je navržena ze systému Porotherm. Stropní konstrukce je provedena z betonových předepjatých dílců. Půdorys tvoří obdélník. Konstrukce střechy je řešena jako plochá jednoplášťová.

The bachelor thesis is a project of a new building of apartment house, The new building is determined for living and services. It is situated in a flat parcel. It is design as a three floors non-basement. The designed from the system Porotherm. The ceiling structure is made of concrete prestressed slabs. Form building is an oblong. Roof structure is designed as a flat roof.
New Building of apartment house
Keywords: Bakalářská práce; bytový dům; třípodlažní; nedposklepený; system Porotherm; betonový předepjatý strop; jednoplášťová střecha; balkon; Bachelor thesis; apartment building with services; three floors; non-basement; Porotherm system; concrete prestressed slabs; flat roof; balcony